Current research in Egyptology 2019 : proceedings of the Twentieth Annual Symposium, University of Alcalá, 17-21 June 2019 - Arranz Cárcamo, Marta, (Access archaeology., 2021)
Presents proceedings from the 20th meeting of the prestigious international student Egyptology conference, held at the University of Alcalá, 2019. 15 papers address a wide range of topics including all periods of ancient Egyptian history and different aspects of its material culture, archaeology, history, society, religion and language.